New Explicit Bounds on Gamidov Type Integral Inequalities for Functions in Two Variables and Their Applications - Kelong Cheng; Chunxiang Guo (Abstract and Applied Analysis)
Some linear and nonlinear Gamidov type integral inequalities in two variables are established, which can give the explicit bounds on the solutions to a class of Volterra-Fredholm integral equations. Some examples of application are presented to show boundedness and uniqueness of solutions of a Volterra-Fredholm type integral equation.